2009
DOI: 10.20870/oeno-one.2009.43.3.797
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of Moroccan grapevine germplasm using SSR markers for the establishment of a reference collection

Abstract: Aims:This study aims to characterize the SODEA ampelographic collection in Meknès, the only germplasm repository in Morocco. To assess the usefulness of this germplasm, a study was conducted to verify the trueness to type of the genotypes and to provide the first database for a reference collection in Morocco. A core collection was then established to define a small sample easier to handel further characterization. Methods and results:Ninety-four grapevine samples from the collection were analyzed using 20 nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 29 publications
(33 reference statements)
3
14
0
Order By: Relevance
“…The accession used here was from the SODEA germplasm bank, a collection created in 1952 in Meknes by Vidal, who collected local vines from different regions, particularly from the Rif (northern Morocco). A comparison of the genetic profile of Djinani and Jaén using 20 SSR recently confirmed that they are synonyms (El Oualkadi et al 2009). This study confirmed the identity of these synonyms and two color sports (rose) ( Table 1) for the SNP markers used.…”
Section: Resultsmentioning
confidence: 84%
“…The accession used here was from the SODEA germplasm bank, a collection created in 1952 in Meknes by Vidal, who collected local vines from different regions, particularly from the Rif (northern Morocco). A comparison of the genetic profile of Djinani and Jaén using 20 SSR recently confirmed that they are synonyms (El Oualkadi et al 2009). This study confirmed the identity of these synonyms and two color sports (rose) ( Table 1) for the SNP markers used.…”
Section: Resultsmentioning
confidence: 84%
“…As a preliminary step toward the search of Moroccan autochthonous cultivars, the content of SODEA (an agricultural development company located in Meknès, Morocco), the only grape collection existing in Morocco, was analysed using SSR markers in order to identify the cultivars (El Oualkadi et al 2009). This collection contains 21 cultivars of Moroccan origin.…”
Section: Introductionmentioning
confidence: 99%
“…The VMC4f3-1and VVIn73 nuSSRs have been already described to be respectively the most and least informative ones by other authors (El Oualkadi et al 2009;Riahi et al 2010) since a higher discrimination power (D) implicates a lower probability of confusion of cultivars (Sefc et al 2000). The expected heterozygosity is a useful measurement to compare with other works since the number of allele per locus is sensitive to the number of cultivars analyzed (Sefc et al 2000;Aradhya et al 2003).…”
Section: Genetic Structurementioning
confidence: 97%